2018
DOI: 10.1029/2018gl077406
|View full text |Cite
|
Sign up to set email alerts
|

Recent Decline in Extratropical Lower Stratospheric Ozone Attributed to Circulation Changes

Abstract: The 1998–2016 ozone trends in the lower stratosphere are examined using the Modern‐Era Retrospective Analysis for Research and Applications Version 2 (MERRA‐2) and related National Aeronautics and Space Administration products. After removing biases resulting from step changes in the MERRA‐2 ozone observations, a discernible negative trend of −1.67 ± 0.54 Dobson units per decade (DU/decade) is found in the 10‐km layer above the tropopause between 20°N and 60°N. A weaker but statistically significant trend of −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(138 citation statements)
references
References 52 publications
(84 reference statements)
11
115
2
Order By: Relevance
“…Both of the models in this work are driven with the MERRA‐2 meteorological reanalysis, and both use versions of NASA's GMI chemical mechanism (Duncan et al, ; Nielsen et al, ). The first model (M2 GMI Replay; Orbe et al, ; Wargan et al, ) runs a previous version of the GMI mechanism, but uses the Replay technique (Orbe et al, ) to recalculate meteorological variables throughout the simulation. The purpose of the Replay technique is to reproduce (“replay”) the MERRA‐2 reanalysis with higher temporal resolution than archived MERRA‐2 products (which are used in the GMI CTM).…”
Section: Data and Model Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of the models in this work are driven with the MERRA‐2 meteorological reanalysis, and both use versions of NASA's GMI chemical mechanism (Duncan et al, ; Nielsen et al, ). The first model (M2 GMI Replay; Orbe et al, ; Wargan et al, ) runs a previous version of the GMI mechanism, but uses the Replay technique (Orbe et al, ) to recalculate meteorological variables throughout the simulation. The purpose of the Replay technique is to reproduce (“replay”) the MERRA‐2 reanalysis with higher temporal resolution than archived MERRA‐2 products (which are used in the GMI CTM).…”
Section: Data and Model Outputmentioning
confidence: 99%
“…Some simulations incorporate observations into a general circulation model to produce an assimilated O 3 product, and in other simulations O 3 is calculated by a chemical mechanism that is driven by a historical meteorological reanalysis and emission inventories (the latter are the focus of this paper). Wargan et al (2018) used three different NASA Modern-Era Retrospective Analysis for Research Applications version 2 (MERRA-2; Gelaro et al, 2017) assimilation and model products and found downward LS O 3 trends from 1998 to 2016 similar to Ball et al (2018), although they attributed the trend mostly to a changing stratospheric circulation.…”
Section: Introduction: the Role For Models In Interpreting Ozone Trendsmentioning
confidence: 99%
“…It is well-known that stratospheric ozone was decreasing since the 1980s, until the reverse of the trend emerged in the late 1990s that marks a turning point in the four-decade history of stratospheric ozone [7,8]. It has been shown in recent literature, e.g., [7,[9][10][11], that ozone in the upper stratosphere follows an upward trend, in contrast to negative, but smaller trends are seen in the lower stratosphere. The behavior of stratospheric ozone after the mid-1990s is dependent on (a) reduction in atmospheric halogens and (b) the slowing of ozone-depleting chemical processes due to the cooling of the stratosphere, which is associated with increases in GHGs.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates. Over some regions, TCO even continues to decrease due to changes in local dynamical and chemical processes (Hood and Soukharev 2005;Zhang et al 2014Zhang et al , 2018Wargan et al 2018), suggesting that long-term ozone variations are highly longitude-dependent. Previous studies pointed out that the trends in the deviation of ozone from the zonal mean over some regions can reach and even exceed the zonal mean ozone trend at that latitude, particularly at 1 3 northern middle latitudes (e.g.…”
Section: Introductionmentioning
confidence: 99%